1992
DOI: 10.1136/jnnp.55.suppl.54
|View full text |Cite
|
Sign up to set email alerts
|

Medical education and the challenge of neurological disability.

Abstract: The neuroscience curriculum should take account of the needs of patients and families and both undergraduate and postgraduate education should be guided by three criteria for quality of medical care-clinical competence, communication (and teamwork), and professional values. The assessment and management of neurological disability requires specific knowledge, skills and attitudes which can be supported by medical education. Suggestions are given on some of the elements which might be included in a curriculum re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Promoting and expanding the pediatric neurology specialty are critical, particularly given that many cases seen by general pediatricians are primarily neurological accounting for up to 30% of all consultations to pediatrics with a high ratio of follow-up visits to new patients [1][2][3]. The assessment and management of neurological disorders requires specific knowledge, skills, and attitudes, which can be supported by medical education [20]. However, some authors have found a decline in general neurology education and that the education was deficient in training physicians to manage gen-eral neurological disorders [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Promoting and expanding the pediatric neurology specialty are critical, particularly given that many cases seen by general pediatricians are primarily neurological accounting for up to 30% of all consultations to pediatrics with a high ratio of follow-up visits to new patients [1][2][3]. The assessment and management of neurological disorders requires specific knowledge, skills, and attitudes, which can be supported by medical education [20]. However, some authors have found a decline in general neurology education and that the education was deficient in training physicians to manage gen-eral neurological disorders [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, completing the pediatric residency did not alter the difficulties they felt in handling neurologic cases. Although the assessment and management of neurologic disorders require specific knowledge, skills, and attitudes, which can be supported by medical education, 12 some investigators have found a decline in general neurology education and that the education was deficient in training physicians to manage general neurologic disorders. 9,13 The education of medical students about epilepsy, for example, a very common pediatric neurology problem, was often fragmented and incomplete.…”
Section: Discussionmentioning
confidence: 99%